Analysis of difficulty level of information system students in communicating English in industrial era 4.0 - Ratih Purwasih; Rahimmulaily Rahimmulaily (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
Purpose of this study is to describe the difficulty level of information system students in communicating English. This study was descriptive quantitative research. The subjects in this study were 100 of second semester information system students and students who repeated (30 people) in 2017/2018 at STMIK Indonesia Padang. The study instrument used was a questionnaires and it were distributed to all research subjects. The processing of questionnaire data used the construct validity test which was supported by the SPSS application. The results of the data analysis of the study shows that the difficulty level of information systems students in communication is categorized at a fairly problematic level with an percentage index of 69%. Therefore, the results of this study can be used as a reference for lecturers in designing learning modules and syllabus that matches with the level of students' ability so that they will be categorized as students who are able to compete in the industrial era 4.0.